Standardization of durian fruit peels (Durio zibethinus Murr.) extract and antioxidant activity using DPPH method - Muhtadi Muhtadi; Utami Ningrum (Universitas Ahmad Dahlan, 2019)
Durian fruit peels (Durio zibethinus Murr.) has been studied previously and reported to have pharmacological activity that has the potential to be antioxidant and antihypercholesterol. The ethanolic extracts of Durian fruit peels contained secondary metabolites, namely flavonoids, polyphenols, carotenes, and saponins. The purpose of this study to determine the non-specific parameters and specific parameters of the ethanol extract of durian fruit peels and to evaluate the antioxidant activity with the DPPH method. Standardization of herbal ingredients is an important thing to do so that the safety and quality of herbal medicines can be maintained. Two different cultivars of durian fruit peels are used, there are Medan and Monthong. The results of non-specific parameters between Medan and Monthong cultivars showed different moisture content (9.71 ± 0.96; 12.06 ± 0.34%, respectively), ash values (1.03 ± 0.20; 1.78 ± 0.07%, respectively), and water content (6.12 ± 0.29; 7.16 ± 0.25% respectively). Medan and Monthong cultivar extracts showed specific parameters showed different organoleptic information such as odor, color, and physical appearance, the content of water soluble compounds (36.39 ± 1.90%), the value of ethanol soluble compounds (40.20 ± 0.19; 45.27 ± 1.02%, respectively), and flavonoid value (472 ± 49.00; 310 ± 13.45 mg/g sample), phenolic value (245 ± 5.15; 148 ± 8.54 mg/g sample). Antioxidant activity was indicated by IC50 values of each extract, namely Medan of 78.83 ± 1.67 µg/mL and Monthong of 72.77 ± 6.60 µg/mL. Statistical tests showed the value of non-specific parameters and specific parameters of the two cultivars not differed significantly.